Syd Hanna: capstone - Hanna, Syd, artist (Colorado State University. Libraries, 2023)
The artist's statement: Functionality is important to me. Many of my pieces are made with usability in mind while challenging the idea of traditional function. Experimentation is a big part of my practice. It is essential to get in the studio and try different materials that can command others to create a balanced relationship. Exploration of saturated colors that clash and battle each other for prominence make for an exciting conversation. Unpredictable textures lead me to color choices that create a synthesis of the two. I begin with a structure; something that creates an undoubted sense of security and familiarity. I use the reliability of structure to allow for ambiguity in other materials. In this body of work, I take the uncontrolled inflation of the foam and find ways to regulate it. Each time the foam is applied it settles and expands in a different way than before, embodying opportunities for chance. The uncertainty of this process excites and challenges me. This triggers a call and response in my process, creating what feels like an instinctive methodology where I fluidly work with, and build upon, the foundation I have created.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: sculpture